Impact of a clinical pharmacist on ultrasound-guided venous thromboembolism screening in hospitalized COVID-19 patients: a pilot prospective study - Laura Gillespie; Rashid Z. Khan; John E. Stillson; Connor M. Bunch; Faisal Salim Shariff; Jacob Speybroeck; Anne Grisoli; Meredith Wierman Schmidt; Htay Phyu; Jason Jablonski; Byars Wells; Daniel H. Fulkerson; et al. (Journal of Pharmaceutical Health Care and Sciences, 2021)
Abstract Background The recognition, prevention and treatment of venous thromboembolism (VTE) remains a major challenge in the face of the recent COVID-19 pandemic which has been associated with significant cardiovascular, renal, respiratory and hematologic complications related to hypercoagulability. There has been little literature thus far on the utility of screening ultrasound and the role of the clinical pharmacist in treating these patients. Methods We present a prospective pilot program of thirty-one consecutive COVID-19 patients who were provided four extremity screening ultrasounds for VTE on admission. This was coordinated by a clinical pharmacist as part of a multidisciplinary approach. Quantitative and qualitative data were recorded with the goal of describing the utility of the clinical pharmacist in ultrasound screening. Data collected include demographics, information on clinical symptoms or signs at presentation, and laboratory and radiologic results during the hospitalization from each individual electronic medical record. Results Nine of the thirty-one patients presented with VTE. Of the nine patients, there were twenty-two total clotted vessels, all of which were asymptomatic. The clinical pharmacist, as the coordinator for a multidisciplinary COVID-19 associated coagulopathy management team, drafted a screening and treatment protocol for anticoagulation prophylaxis and therapy of VTE after ultrasound findings. Conclusion VTE screening of hospitalized COVID-19 patients reveals a significant number of asymptomatic VTEs and justifies diagnostic, prophylactic, and treatment measures coordinated by a clinical pharmacist.